2015
DOI: 10.1158/1055-9965.epi-14-1054
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Levels of the Lung Carcinogen NNAL and Its Glucuronides in the Urine of Cigarette Smokers from Five Ethnic Groups with Differing Risks for Lung Cancer

Abstract: Background Results of the Multiethnic Cohort study (MEC) demonstrated that, for the same quantity of cigarettes smoked, African Americans (AfrAm) and Native Hawaiians (NH) have a higher risk of lung cancer compared to Whites, whereas Latinos (LA) and Japanese Americans (JA) have a lower risk. We hypothesize that the uptake and/or metabolism of the lung carcinogen 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNK) could explain the differences in lung cancer risk. Methods We measured urinary 4-(methylnitros… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
46
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 47 publications
4
46
0
Order By: Relevance
“…This methodology incorporates several sample processing steps and corresponding LC-MS runs using up to 180 μL of urine specimen and a nano-LC-MS instrument (35). This method is sensitive, reaching levels as low as 0.10 nM for the quantification of urinary free NNAL (35, 46). Limitations of this procedure include the fact that NNAL- N -Gluc and NNAL- O -Gluc are not directly measured, and that the ( R )- and ( S )-NNAL- O -Gluc diasteriomers are not measured individually.…”
Section: Discussionmentioning
confidence: 99%
“…This methodology incorporates several sample processing steps and corresponding LC-MS runs using up to 180 μL of urine specimen and a nano-LC-MS instrument (35). This method is sensitive, reaching levels as low as 0.10 nM for the quantification of urinary free NNAL (35, 46). Limitations of this procedure include the fact that NNAL- N -Gluc and NNAL- O -Gluc are not directly measured, and that the ( R )- and ( S )-NNAL- O -Gluc diasteriomers are not measured individually.…”
Section: Discussionmentioning
confidence: 99%
“…24, 12, 1825 In contrast to the relatively high tumorigenicity exhibited by both ( R )- and ( S )-NNAL, glucuronidated NNAL (NNAL-Gluc) is non-tumorigenic after subcutaneous injection into A/J mice. 26 It has been shown that NNAL glucuronides are formed extensively in human liver microsomes (HLM).…”
Section: Introductionmentioning
confidence: 99%
“…20, 27 The NNAL enantiomers and their glucuronides can also be detected in the urine of past and current smokers. 3, 2225, 28–32 It has been found that while ( S )-NNAL is stereoselectively retained in rat lung and has a higher tumorigenicity than ( R )-NNAL, ( R )-NNAL exhibits a higher rate of glucuronidation in rats 3336 and the A/J mouse. 26, 36 However, studies indicate that ( S )-NNAL may be stereo-selectively retained in smokeless tobacco users 37 but exhibits a higher rate of glucuronidation in the patas monkey.…”
Section: Introductionmentioning
confidence: 99%
“…Results from several human studies demonstrate that such a ratio varies among individuals (Carmella et al, 1995;Park et al, 2015). It is possible that individuals with a low basal urinary ratio of NNAL-gluc to free NNAL may more likely benefit from DHM in reducing their lung cancer risk via enhancing/restoring their detoxification capacity.…”
mentioning
confidence: 99%